Exploring the impact of experimental sleep restriction and sleep deprivation on subjectively perceived sleep parameters. (5th June 2018) - Maric, Angelina; Bürgi, Manuel; Werth, Esther; Baumann, Christian R.; Poryazova, Rositsa
Summary: We aimed to investigate the effect of increased sleep pressure and shortened sleep duration on subjective sleep perception in relation to electroencephalographic sleep measures. We analyzed the data from a study in which 14 healthy male volunteers had completed a baseline assessment with 8 hr time in bed, a sleep deprivation (40 hr of wakefulness) and a sleep restriction protocol with 5 hr time in bed during 7 nights. In this work, we assessed perception index, derived through dividing the subjectively perceived total sleep time, wake after sleep onset and sleep latency duration by the objectively measured one at each condition. We found that total sleep time was subjectively underestimated at baseline and shifted towards overestimation during sleep restriction and after deprivation. This change in accuracy of subjective estimates was not associated with any changes in sleep architecture or sleep depth. Wake after sleep onset was significantly underestimated only during sleep restriction. Sleep latency was always overestimated subjectively without any significant change in this misperception across conditions. When comparing accuracy of subjective and actimetry estimates, subjective estimates regarding total sleep time and wake after sleep onset deviated less from electroencephalography derived measures during sleep restriction and after deprivation. We conclude that self‐assessments and actimetry data of patients with chronic sleep restriction should be interpreted cautiously. The subjectively decreased perception of wake after sleep onset could lead to overestimated sleep efficiency in such individuals, whereas the underestimation of sleep time and overestimation of wake after sleep onset by actimetry could lead to further underestimated sleep duration.